Kajian Pengembangan Internet of Things (IoT) pada Sektor Pertanian di Kabupaten Ngada, Nusa Tenggara Timur - Goda, Karina Dhena; Neta, Agusto Del Piero Stein (Universitas Ma'arif Nahdlatul Ulama Kebumen, 2024)
The Internet of Things (IoT) can significantly transform the agricultural sector by introducing various applications that help enhance efficiency, productivity, and sustainability in the agricultural sector of Ngada Regency. This research aims to examine the landscape of potential IoT development for implementation in the agricultural sector of Ngada Regency as well as to point out the possibilities and challenges of developing agricultural IoT in Ngada. This study is composed of comprehensive literature reviews and field observations. The results indicate that IoT applications already implemented in other regions also have great potential for development in Ngada. The availability of telecommunications network infrastructure, access to IoT hardware and software, government support for agricultural technology development, and human resources make IoT feasible to be implemented in Ngada Regency. This research is limited to examining the opportunities and challenges of IoT implementation, thus further research is needed on development strategies for small, medium, and large scales to assist in mapping the IoT development plan in Ngada. This research can serve as a reference for further studies on developing IoT-based agricultural system prototypes in Ngada